Wnt2 Contributes to the Development of Atherosclerosis - Zhang, Jinyu; Rojas, Samuel; Singh, Sanjay; Musich, Phillip R.; Gutierrez, Matthew; Yao, Zhiqiang; Thewke, Douglas; Jiang, Yong (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis, is a chronic inflammatory disease, characterized by the narrowing of the arteries resulting from the formation of intimal plaques in the wall of arteries. Yet the molecular mechanisms responsible for maintaining the development and progression of atherosclerotic lesions have not been fully defined. In this study, we show that TGF-β activates the endothelial-to-mesenchymal transition (EndMT) in cultured human aortic endothelial cells (HAECs) and this transition is dependent on the key executor of the Wnt signaling pathway in vitro. This study presents the first evidence describing the mechanistic details of the TGF-β-induced EndMT signaling pathway in HAECs by documenting the cellular transition to the mesenchymal phenotype including the expression of mesenchymal markers α-SMA and PDGFRα, and the loss of endothelial markers including VE-cadherin and CD31. Furthermore, a short hairpin RNA (shRNA) screening revealed that Wnt2 signaling is required for TGF-β-mediated EndMT of HAECs. Also, we found that LDLR-/- mice fed on a high-fat western-type diet (21% fat, 0.2% cholesterol) expressed high levels of Wnt2 protein in atherosclerotic lesions, confirming that this signaling pathway is involved in atherosclerosis in vivo. These findings suggest that Wnt2 is an important driver of atherosclerotic plaque growth and may provide a potential target for specific therapeutic intervention aimed at controlling this disease.